Respostas

2016-09-19T09:31:01-03:00
A² = b² + c² - 2 bc cosα 

(Onde α é o ângulo oposto ao lado a) 

Isolando cosα: 

2bc cosα = b² + c² - a² 

cosα = (b² + c² - a²)/2bc 

Sendo a = √6 ; b = 2√3 e c = (3+√3) , temos: 

b² + c² - a² = (2√3)² + (3+√3)² - (√6)² = 12 + 9 + 6√3 + 3 - 6 = 18 + 6√3 = 6(3+√3) 

2bc = 2. 2√3(3+√3) = 4√3(3+√3) = 12√3 + 12 = 12(√3+1) 


cosα = 6(3+√3)/ 12(√3+1) 

cosα = (3+√3)/ 2(√3+1) 

Racionalizando o denominador: 

cosα = (3+√3)(√3-1) / 2(√3+1)(√3-1) 

cosα = (3√3 -3 + 3 - √3)/ 2(3-1) 

cosα = 2√3 / 4 

cosα = √3 /2 

α = arccos(√3 /2) = 30°